Improving efficiency of public cadastral procedures through customer-orientation - Sulonen, Kimmo (Tampere University dissertations, ISSN 2489-9860, 2020)
Tiivistelmä.
Keywords: kiinteistötoimitus; prosessit; kehittäminen; asiakaslähtöisyys